2022
DOI: 10.1002/lt.26547
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐rapid whole genome sequencing: A paradigm shift in the pre‐transplant evaluation of neonatal acute liver failure

Abstract: To the editor, Neonatal acute liver failure (NALF) is an ominous disorder resulting from severe hepatocellular injury and manifesting as rapid deterioration of liver function. Common etiologies of NALF include gestational alloimmune liver disease (GALD), viral infection (VI), familial hemophagocytic lymphohistiocytosis (fHLH), mitochondrial hepatopathy (MH), toxic metabolic hepatopathy (TMH), and genetic cholestasis (GC), [1] although most cases of NALF remain idiopathic. [2] Evaluation for liver transplantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…rGS has demonstrated improved diagnostic rate and clinical utility as compared to other forms of genetic testing with reduced overall costs of care [9,10]. Our group has also shown the utility of rapid genome sequencing as first-line testing in neonatal acute liver failure, for which the gold standard diagnostic test had previously been liver biopsy, which is similarly often unfeasible in critically ill neonates [11]. While rGS represents an important step forward in timely and comprehensive diagnosis of severe neonatal hypoxemic respiratory failure, determining pathogenic significance of variants not previously described, as with other types of genetic testing, remains a challenge.…”
Section: Discussionmentioning
confidence: 97%
“…rGS has demonstrated improved diagnostic rate and clinical utility as compared to other forms of genetic testing with reduced overall costs of care [9,10]. Our group has also shown the utility of rapid genome sequencing as first-line testing in neonatal acute liver failure, for which the gold standard diagnostic test had previously been liver biopsy, which is similarly often unfeasible in critically ill neonates [11]. While rGS represents an important step forward in timely and comprehensive diagnosis of severe neonatal hypoxemic respiratory failure, determining pathogenic significance of variants not previously described, as with other types of genetic testing, remains a challenge.…”
Section: Discussionmentioning
confidence: 97%
“…The differential diagnosis for NALF includes nHLH, gestational alloimmune liver disease (GALD), sepsis, viral infections, metabolic hepatology, transient abnormal myelopoiesis, and hypoperfusion injury. 8,9 In an epidemiologic analysis, Balakumar and colleagues (2022) found that liver failure occurred in 35% of nHLH cases and that liver failure was the only organ dysfunction independently associated with increased mortality on multivariable analysis. 7 The epidemiologic methodology used by Balakumar et al ( 2022) utilized ICD-9 and ICD-10 codes and, similar to other studies that use large databases, was limited by coding accuracy.…”
Section: Treatment and Outcomementioning
confidence: 99%
“…The clinical presentation of nHLH is diverse and can include fever, hydrops, neonatal acute liver failure (NALF), cytopenias, respiratory distress, and encephalopathy—all of which have their own unique differential diagnoses that may be more common causes of critical illness in neonates 6 . For example, the differential diagnosis of NALF includes nHLH, infection, gestational alloimmune liver disease, liver ischemia, metabolic hepatology, and transient abnormal myelopoiesis 8,9 . A proper understanding and index of suspicion of nHLH is clinically necessary for pediatric hematologists/oncologists and intensivists to diagnose nHLH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation